Pojavnost depresije v povezavi s spremljajočimi obolenji glede na izid zgodnje rehabilitacije pri bolnikih po preboleli možganski kapi v SB Celje - Nestorov, Šadeja (Rehabilitacija (Ljubljana), 2024)
Background: Stroke is the second leading cause of disability and death worldwide, thus presenting an important public health problem. Post-stroke depression is the most common neuropsychiatric consequence, affecting 18 to 78 % of these patients in the first two years. The outcome of the functional state of these patients depends on early rehabilitation treatment. The latter is carried out in a multidisciplinary form at the Neurological department of the Celje General Hospital. The aim of our research was to determine the incidence of depression and accompanying diseases regarding the functional outcome after early rehabilitation treatment of these patients. Methods: The study included patients who suffered a stroke (ischemic or cerebral hemorrhage) and were hospitalized at the Neurological department of the Celje General Hospital from October 1st 2020 to the end of April 2021. From the medical records, we collected data on the type of stroke and accompanying diseases and performed an assessment of functioning upon admission and discharge. Results: The research included 85 patients. The comparison between admission and discharge showed statistically significant differences in Functional independence measure, Modified Rankin Scale, National Institutes of Health Stroke Scale and Stroke Adapted Sickness Profile. There were no statistically significant differences for Hospital Anxiety and Depression Scale and Montreal cognitive assessment values. Conclusion: There were no statistically significant differences in the incidence of depression after stroke in our sample of patients at the admission and discharge; it occurred in a similar proportion as in previous studies of other authors. To investigate the incidence and the impact of depression on the outcome of early rehabilitation, additional research on a larger sample would be needed.
Keywords: cognitive functions; depresija; Depression; izid; kognitivne funkcije; motor functions; motorične funkcije; možganska kap; outcome; rehabilitacija; rehabilitation; Stroke